Effect of Magnesium-Based Coatings on Titanium or Zirconia Substrates on Bone Regeneration and Implant Osseointegration- A Systematic Review - Almehmadi, Ahmad H (Frontiers in Materials, 2021)
ABSTRACT Magnesium (Mg) is an essential trace element that has a significant role in the human body through its effects on bone metabolism. It has various applications in orthopedics and dentistry and the interest of this systematic review lies in its potential role as a dental implant surface coating. The dental implants can fail at different stages starting with its osseointegration phase to the restorative stage in the oral cavity. The biological loss of bone integration to the implant surface has been classified as one of the primary reasons for dental implant failure. There have been numerous strategies that have been shown to compensate this reason for implant failure, among which are the dental implant surface coatings. These coatings have been shown to improve osteoblastic adhesion as well as the process of osseointegration. There are numerous studies in the existing literature that have analyzed the effects of Mg-based coatings on cellular as well as biological processes in bone-implant integration. A systematic search of various databases yielded 175 articles, of which 14 in-vitro and experimental animal studies that analyzed the effect of Mg-based coatings and compared it to other coatings or no surface coatings were included in this systematic review. The main outcomes of this systematic review have been cellular behavior, osseointegration, and osteogenic markers and the effects of Mg-based coatings in these parameters have been highlighted in this review.